2003
DOI: 10.1152/ajprenal.00290.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transport of cimetidine by flounder and human renal organic anion transporter 1

Abstract: Burckhardt. Transport of cimetidine by flounder and human renal organic anion transporter 1. Am J Physiol Renal Physiol 284: F503-F509, 2003. First published November 12, 2002 10.1152/ajprenal.00290.2002The H 2-receptor antagonist cimetidine is efficiently excreted by the kidneys. In vivo studies indicated an interaction of cimetidine not only with transporters for basolateral uptake of organic cations but also with those involved in excretion of organic anions. We therefore tested cimetidine as a possible su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
1
26
1
Order By: Relevance
“…Thus, the results of studies using cimetidine as an OCT inhibitor have to be carefully interpreted considering the effect of this substrate on the OAT system. Burkhardt et al (2003) have already demonstrated that hOAT1 mediated the uptake of cimetidine (17). However, we noted that cimetidine inhibited the PAH uptake mediated by hOAT1 in a combination of competitive and noncompetitive manners.…”
contrasting
confidence: 41%
“…Thus, the results of studies using cimetidine as an OCT inhibitor have to be carefully interpreted considering the effect of this substrate on the OAT system. Burkhardt et al (2003) have already demonstrated that hOAT1 mediated the uptake of cimetidine (17). However, we noted that cimetidine inhibited the PAH uptake mediated by hOAT1 in a combination of competitive and noncompetitive manners.…”
contrasting
confidence: 41%
“…Figure 8 shows the effect of 1 mM concentrations of unlabeled PAH and CIM on the uptake of radiolabeled PAH and CIM into CHO cells that stably expressed rbOAT1. PAH (1 mM), as expected, reduced accumulation of 0.3 M [ observed by Burckhardt et al (7). As shown in Fig.…”
supporting
confidence: 89%
“…We also found that the rabbit ortholog of OAT3 interacts with CIM with higher apparent affinity at elevated pH, consistent with the view that the neutral species binds more effectively to the transporter than does the charged species (unpublished observations). However, ES transport showed the same sensitivity to pH, despite the fact that over the tested pH range (pH [7][8] there is no significant change in the concentration of the protonated species of ES. Consequently, it remains equivocal if the charge status of CIM plays a role in its binding to rabbit OAT3.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As a zwitterion at physiological pH values (pKa1 = 6.1, pKa2 = 8.7), ciprofloxacin might also be able to interact with both OAT and OCT [23]. Cimetidine, an inhibitor of OCT as well as OAT 1 and 3 [24][25][26], has been shown to decrease the renal clearance of several quinolones, e.g. gemifloxacin, enoxacin, temafloxacin and ofloxacin [27,28].…”
Section: Discussionmentioning
confidence: 99%